2019
DOI: 10.3390/ma12223774
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Voids Characteristics in an Asphalt Mixture Exposed to Salt Erosion Based on CT Images

Abstract: The performance of an asphalt mixture will deteriorate under the condition of salt erosion, but there are different opinions on the mechanism of deterioration. Few studies have focused on the relation between the change of void characteristics and performance deterioration of an asphalt mixture exposed to salt erosion. To explore the relation between the air voids characteristics of an asphalt mixture and mechanical damage under salt erosion, the mechanical damage in an asphalt mixture was measured by splittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The boundary of different components in the CT image is clear and continuous, and there is no component information missing in the CT image of asphalt pavement. The effectiveness of the OTSU algorithm in segmenting the aggregates and voids of the asphalt mixture has also been verified in some of the literature [ 24 , 25 , 26 ]. Obviously, segmenting different components in a CT image of a pavement core sample by the improved OTSU threshold separation method is reliable.…”
Section: Separation Of Mixture Components For Asphalt Pavementmentioning
confidence: 82%
“…The boundary of different components in the CT image is clear and continuous, and there is no component information missing in the CT image of asphalt pavement. The effectiveness of the OTSU algorithm in segmenting the aggregates and voids of the asphalt mixture has also been verified in some of the literature [ 24 , 25 , 26 ]. Obviously, segmenting different components in a CT image of a pavement core sample by the improved OTSU threshold separation method is reliable.…”
Section: Separation Of Mixture Components For Asphalt Pavementmentioning
confidence: 82%
“…The main working principle of spreading the deicing salt snow melting agent is based on the freezing point reduction theory [ 14 , 15 ]. The so-called freezing point refers to the temperature when a substance reaches the state of solid-liquid coexistence.…”
Section: Introductionmentioning
confidence: 99%
“…They found that there is a linear relationship between the splitting strength of asphalt mixture in the salt erosion condition and its void characteristics. The crystallization pressure caused by salt will accelerate the development of internal pores of asphalt mixture, resulting in a decrease in its mechanical properties [ 14 ]. Wang et al investigated the pavement performances of asphalt mixture containing salt-storage aggregates with the function of snow melting [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, asphalt pavement is prone to high temperature rutting, low temperature cracking, water damage and spalling [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. In some special natural environments, especially in coastal areas and northwest saline soil areas, corrosion medium such as sulfate–chloride would lead to the serious damage of asphalt pavement after several years of service, and the service life of the road is greatly reduced [ 11 , 12 , 13 , 14 , 15 ]. In addition, the road surface is easy to freeze in winter.…”
Section: Introductionmentioning
confidence: 99%
“…The method of spreading deicing salt, a snow melting agent with the function of quick deicing and snow melting, could be considered an effective method to solve the problem of traffic jams and prevent the pavement from continuing to freeze [16,20]. The theory principle of spreading deicing salt, a snow melting agent, is generally based on the freezing point reduction theory [13,15]. The so-called freezing point refers to the temperature when Materials 2021, 14, 3089 2 of 14 a substance reaches the state of solid-liquid coexistence and two-phase equilibrium.…”
Section: Introductionmentioning
confidence: 99%